Fundamentals of financial management - Brigham, Eugene F., 1930- (South-Western Cengage Learning, 2013)
With the same contemporary approach and dynamic examples that made previous editions so popular, this fully revised thirteenth edition of FUNDAMENTALS OF FINANCIAL MANAGEMENT continues to provide students with a focused understanding of today's corporate finance and financial management.